Stock assessment of the Indian mackerel Rastrelliger kanagurta (Cuvier, 1817) from Muscat coast, Oman - Jayabalan, N.; Zaki, S.; Al-Marzouqi, A.; Al-Kiyumi, F. (Indian Journal of Fisheries, 2016)
Assessment of age, growth and stock parameters was carried out for the Indian mackerel Rastrelliger kanagurta (Cuvier) along the Muscat coast of Oman between October 2007 and September 2009. The length-weight relationship of the fish indicated the ‘a’ value as 0.0101 and ‘b’ value as 3.0589. The length based von Bertalanffy growth (VBG) parameters L∞ K and t0 estimated were 37.54 cm, 1.0 y-1 and -0.17 y respectively. The estimates of mortality rates showed the annual total mortality (Z) to be 2.98, the natural mortality (M) 1.62 and fishing mortality (F) 1.36. The MSY estimated by Cadima’s estimator was 859 t and the predicted value by yield analysis stood at 1,273 t. The calculated exploitation rate (E) was 0.46. The Yw/R at F = 1.6 was 48 g. Estimates of higher MSY than the current yield, lower fishing mortality than natural mortality and lower E indicate scope for increase in yield of R. kanagurta from Muscat region.